FRI0555 INFLUENCE OF ANTI-TUMORNECROSIS FACTOR (TNF) DRUG IMMUNOGENICITY ON THE TREATMENT EFFECTIVENESS IN JUVENILE IDIOPATHIC ARTHRITIS (JIA) USING SERUM CALPROTECTIN AS A DISEASE ACTIVITY MARKER. MULTICENTER STUDY. ITACA STUDY. (June 2019) - Calvo, Inmaculada; Modesto, Consuelo; Montoro, Maria; Laiz, Begoña; Iglesias, Estibaliz; Quesada-Masachs, Estefanía; Lopez-Montesinos, B; Bou, R; Gonzalez-Fernández, M.I.; Fornés, J; Rodriguez, A; Sanchez, Jj; et al.
Abstract : Background: There is a lack of evidence about the loss of efficacy of anti-TNF agents in JIA and its possible relation to the immunogenicity generated. In the last years there has been interest in the role of serum calprotectin in children diseases, including JIA. Objectives: To assess the immunogenicity and bioavailability of anti-TNF drugs, their relationship with disease activity and the clinical utility of serum calprotectin in monitoring JIA patients. Methods: This is a 12-month prospective, multicenter, non-interventional, observational study. Patients from 2 to 18 years diagnosed with non-systemic JIA according to ILAR criteria and receiving treatment with IFX, ADA or ETN were included. The patients were evaluated using the CHAQ and the juvenile arthritis disease activity score (JADAS 71) and determination of anti-TNF drug, anti-drug antibody and calprotectina serum levels were performed. Results: 222 patients were included. At month 12, 181 (81.5%) continued receiving treatment, and 205 (94.5%) had positive serum levels of anti-TNF drug (96.2% of ETN, 93.5% of ADA and 66.7% of IFX) at baseline and at 12 months serum levels were positive in 161 (95.3%) patients (97.5% ETN, 93.2% ADA and 100% IFX). In total, 16 (7.3%) patients presented anti-drug A (1 of 106 anti-ETN, 13 of 109 anti-ADA, 2 of 3 anti-IFX) at baseline and 4 patients (2.4%) (0 of 81 anti-ETN, 4 of 88 anti-ADA, 0 of 1 anti-IFX) at 12 months. Regarding the relationship between anti-TNF levels or anti-drug Abs, disease activity, and functional disability overall, statistically significant differences were not observed between the groups. Patients with high levels of serum calprotectin at the baseline visit (16 of 216) showed higher JADAS-71 score [1.23 (2.06 SD) vs. 2.06 (3.44 SD)] and CHAQ [0.11 SD (0.28 SD)] vs 0.17 (0.40 SD)] compared with normal calprotectin group, although no statistically significant differences were observed (p = 0.066 and p = 0.288) between the groups with a normal and high level of serum calprotectin and the number of patients was small. Conclusion: The low prevalence of anti-drug Abs observed was in consonance with the high proportion of patients with a positive serum level of anti-TNF drug. These data suggest an appropriate management of the long-term treatment of Spanish JIA patients, who showed a maintained inactive disease/low disease activity state and a very low functional disability state as a consequence of a low immunogenicity and good bioavailability of anti-TNF drugs. Disclosure of Interests: Inmaculada Calvo Grant/research support from: received research grants from Pfizer, Roche, Novartis, Clementia, Sanofi, MSD, BMS and GSK, Consultant for: Advisory boards: Novartis, AbbVie, Speakers bureau: AbbVie, Roche, Novartis, SOBI, Consuelo Modesto: None declared, Maria Montoro Shareholder of: Maria Montoro is employee of and shareholder in Pfizer, Employee of: Maria Montoro is employee of and shareholder in Pfizer, Begoña Laiz: None declared, Estibaliz Iglesias: None declared, Estefanía Quesada-Masachs: None declared, B Lopez-Montesinos: None declared, R Bou: None declared, M.I. Gonzalez-Fernández: None declared, J Fornés: None declared, A Rodriguez: None declared, jJ Sanchez: None declared, J Calzada: None declared, Tamara Rodriguez: None declared, Mireia Lopez Corbeto: None declared, Susana Gómez Employee of: I am a current employee of Pfizer., Jordi Anton Grant/research support from: JA has received grant/research support, consulting fees and/or honoraria from AbbVie, Alexion, BMS, ChemoCentryx, Gebro, GSK, Novartis, Novimmune, Pfizer, Roche, Sanofi and Sobi, Consultant for: JA has received grant/research support, consulting fees and/or honoraria from AbbVie, Alexion, BMS, ChemoCentryx, Gebro, GSK, Novartis, Novimmune, Pfizer, Roche, Sanofi and Sobi